MP19: Creation and implementation of an educational emergency medicine clinical handbook. (May 2019) - Anjum, O.; Syed, S.
Abstract : Innovation Concept : Medical students often face challenges when entering clerkship. The abundance of teaching tools and online resources make it difficult for learners to navigate and apply knowledge in a clinical setting. Although valuable study aids exist across Emergency Medicine (EM) clerkship curriculums, a convenient resource tailored to junior learners for on-shift use is lacking. We created an academic resource with the intent of assessing student engagement with the handbook.Methods : Ottawa's Clerkship Guide to Emergency Medicine was developed using information from a commonly used EM textbook and relevant literature. After a comprehensive peer-review by staff EM physicians, the resource was published online and made available to learners in March 2018. To assess utility of this resource, a national survey was administered followed by a Likert-type analysis. Website metrics and the survey results were used to guide a sustainable model for annual student-driven resource updates.Curriculum, Tool or Material : The handbook contains high-yield EM topics organized into one-page summaries. The main sections include resuscitation, symptoms-based approach, and medical emergencies. Students can access the handbook online, via mobile app, or use a printable version. Over 7300 unique downloads have occurred since launch. Our national survey revealed that of the total respondents (N = 171, 93.6% 3rd-year clerks, 31.6% uOttawa students), 97.1% (n = 166) had used the handbook on shift. A majority were able to find an answer to their clinical question either fully (53%, n = 88) or partially (46.4%, n = 77) and many would recommend this resource as-is (62.7%, n = 104) or with some modifications (34.3%, n = 57). Compared to the student's preferred clinical resource, mean Likert-type scores showed a significant (p < 0.01) positive difference in favor of the handbook regarding themes of organization (3.83 vs. 4.38), length (3.43 vs. 4.76) and ease in accessibility (3.46 vs. 4.79).Conclusion : The value of this handbook for junior learners entering their acute care rotation is evident. We demonstrated that student uptake of this handbook was robust. Compared to commonly used resources, students felt this handbook was more organized, concise in length, and easy to integrate into their clinical workflow. Implementation of this handbook across Canadian EM curriculums may bridge the EM knowledge gap in junior learners and off-service residents.